(untitled) (Palíndromo, 2016)
This article is the result of a qualita- tive research carried out in Pericot Scho- ol in Girona during internship period of Grau de Mestre d’Educació Primària and in art education speciality. The study has had the children in second of primary as sample and a tracking group formed by the specialist teacher, the research men- tor and project author. The main purpo- se of the article is to fight the problem of misconceptions about the beginnings and consolidation of writing and to find appropriate graphics activities that bring benefits that can end up producing en- trepreneurial ideas. The graphics focus is analysed both from the writing in linguis- tic aspect and from artistic aspect. The educational intervention, as an empiri- cal part of the research, aims to provide date of all learning process, both identi- fication and analysis aspects, and imple- mentation and interpretation, through to creation.